Subsidies and Interacting Crop Market Dynamics - Behnert, Marika; Graupner, Sören; Süssmuth, Bernd (Journal of Applied Nonlinear Dynamics, 2026)
Economically motivated crop rotation has been proposed to model coupled agricultural markets. The resulting supply-sided behavior generates a wealth of complex dynamics. Since centuries most Western economies established substantial agricultural subsidies that we show to be both persistent and differentiated by variety. We incorporate differential subsidies and study whether this changes implied dynamics of interacting crop markets. Our findings contrast with single-crop model predictions inasmuch we find subsidy differentials for rotated crops to exert stabilization.